Characterization and Roles of Cherry Valley Duck NLRP3 in Innate Immunity During Avian Pathogenic Escherichia coli Infection - Li, Rong; Lin, Jing; Hou, Xiaolan; Han, Shaojie; Weng, Hongyu; Xu, Ting; Li, Ning; Chai, Tongjie; Wei, Liangmeng (Frontiers in Immunology, 2018)
The nucleotide-binding oligomerization domain-like receptor (NLR) pyrin domain containing 3 (NLRP3) is a pattern recognition receptor that is involved in host innate immunity and located in the cytoplasm. In the present study, the full-length cDNA of Cherry Valley duck NLRP3 (duNLRP3) (2805 bp encode 935 amino acids) was firstly cloned from the spleen of healthy Cherry Valley ducks, and the phylogenetic tree indicated that the duNLRP3 has the closest relationship with Anas platyrhynchos in the bird branch. According to quantitative real-time PCR analysis, the duNLRP3 mRNA has a broad expression spectrum in healthy Cherry Valley duck tissues, and the highest expression is in the pancreas. There was significant up-regulation of duNLRP3 mRNA expression in the liver and down-regulation in the spleen after infection with avian pathogenic Escherichia coli (APEC) O1K1, especially at 3 days after the infection. Ducks hatched from NLRP3-lentiviral vector-injected eggs had significantly higher duNLRP3 mRNA expression in the liver, spleen, brain, and cecum, which are tissues usually with lower background expression. The mRNA expression levels of inflammatory cytokines IL-1β, IL-18, and TNF-α significantly increased after the APEC infection in those tissues. The bacterial content in the liver and spleen decreased significantly compared with the NC-lentiviral vector-injected ducks. In addition, in the duck embryo fibroblasts, both of the overexpression and knockdown of duNLRP3 can trigger the innate immune response during the E. coli infection. Specifically, overexpression induced antibacterial activation, and knockdown reduced the antibacterial activity of the host cells. The IL-1β, IL-18, and TNF-α mRNA expressions showed up-regulation or down-regulation. The results demonstrate that duNLRP3 has a certain antibacterial activity during E. coli infection. These findings also contribute to better understanding the importance of duNLRP3 in regulating the inflammatory response and the innate immune system of ducks.